Azhari, Ainul PENGARUH FILM ANIMASI TERHADAP PERKEMBANGAN ANAK USIA DINI DALAM BERTINGKAH LAKU DENGAN ETIKA ISLAM - Ainul Azhari (Universitas Islam Syekh-Yusuf, 2023)
In this era of globalization, technology is developing very rapidly and is a support in activities. Such as television which is electronic media that almost all evels of society have on television displaying various kind of programs that are useful in conveying new and entertaining information. One of them is animated films that are loved by children. This can have an impact on children???s development in behaving according to what children see on television, because early childhood is very easy to imitate what they see. The method applied in this research is library research (library search, where in collecting data most of it is obtained from literature and references, both from books, scientific journals, electronic books (e-books), and the internet related to the research theme